Assessment of the psycho-emotional state in pregnant women with hypertensive disorders using the stai and PSS-10 psychometric instruments - Sіusіuka, V. H.; Kyrychenko, M. M.; Сюсюка, Володимир Григорович; Кириченко, Михайло Михайлович (My University, 2025)
Hypertensive disorders during pregnancy, such as gestational hypertension and preeclampsia, remain among the leading causes of maternal and perinatal complications. In addition to physiological risk factors, the psycho-emotional state of pregnant women plays a critical role in influencing obstetric outcomes. Recent studies have highlighted the association between elevated levels of psychological stress and anxiety and the development or worsening of hypertensive complications. This study aimed to assess perceived stress, state anxiety, and trait anxiety in pregnant women diagnosed with hypertensive disorders using validated psychometric instruments. A total of 65 pregnant women participated in the study: 35 with hypertensive complications and 30 pregnant women without diagnosed hypertensive disorders. Psychological assessment was performed using the State-Trait Anxiety Inventory (STAI) and the Perceived Stress Scale (PSS-10). Comparative analysis revealed significantly higher levels of state and trait anxiety and perceived stress in the hypertensive group. Median STAI-S and STAI-T scores were 44.00 (IQR: 40.00– 48.50) and 51.00 (IQR: 46.00–59.00), respectively, while the perceived stress score reached a median of 28.00 (IQR: 24.00–32.50). In the control group, these values were substantially lower: STAI-S – 31.00 (IQR: 28.25–34.00), STAI-T – 36.00 (IQR: 33.25–39.00), and PSS-10 – 20.50 (IQR: 17.00–24.00) (all p < 0.05). High trait anxiety (STAI-T ≥ 45) was identified in 85.71% of the hypertensive group, and elevated perceived stress (PSS-10 ≥ 32) was observed in 28.57% of cases. Statistically significant correlations were found between perceived stress and both state and trait anxiety, reflecting a close interrelationship between different dimensions of emotional distress in this population. Гіпертензивні розлади під час вагітності, зокрема гестаційна гіпертензія та прееклампсія, залишаються серед провідних причин материнських і перинатальних ускладнень. Окрім фізіологічних факторів ризику, важливу роль у впливі на перебіг вагітності відіграє психоемоційний стан жінки. Останні дослідження підкреслюють зв’язок між підвищеним рівнем психологічного стресу, тривожності та розвитком або погіршенням перебігу гіпертензивних ускладнень. Метою цього дослідження було оцінити рівень сприйнятого стресу, ситуативної та особистісної тривожності у вагітних із гіпертензивними розладами з використанням валідизованих психодіагностичних інструментів. У дослідженні взяли участь 65 вагітних жінок: 35 з гіпертензивними розладами під час вагітності та 30 з без подібних ускладнень. Психологічне оцінювання проводилося за допомогою шкали тривожності Спілбергера (STAI) та шкали сприйнятого стресу (PSS-10). Порівняльний аналіз виявив достовірно вищі рівні ситуативної та особистісної тривожності, а також сприйнятого стресу в групі вагітних з гіпертензивними розладами. Медіанні значення STAI-S і STAIT становили відповідно 44,00 (IQR: 40,00–48,50) та 51,00 (IQR: 46,00–59,00), а показник PSS-10 – 28,00 (IQR: 24,00–32,50). У контрольній групі ці показники були значно нижчими: STAI-S – 31,00 (IQR: 28,25–34,00), STAI-T – 36,00 (IQR: 33,25–39,00), PSS-10 – 20,50 (IQR: 17,00–24,00) (у всіх випадках p < 0,05). Високий рівень особистісної тривожності (STAI-T ≥ 45) був виявлений у 85,71% жінок основної групи, а підвищений рівень сприйнятого стресу (PSS-10 ≥ 32) – у 28,57%. Статистично значущі кореляції були виявлені між рівнем сприйнятого стресу та обома типами тривожності, що відображає тісний взаємозв’язок між різними проявами емоційного напруження в цього контингенту жінок.
Оцінювання психоемоційного стану вагітних з гіпертензивними розладами на основі психодіагностичних інструментів STAI та PSS-10
Keywords: pregnancy; hypertensive disorders; gestational hypertension; preeclampsia; perceived stress; trait anxiety; state anxiety; State-Trait Anxiety Inventory; STAI; Perceived Stress Scale; PSS-10; psychometric assessment; psychological evaluation; pregnancy complications; psycho-emotional state; psychological stress; antenatal care; psychodiagnostics; вагітність; гіпертензивні розлади; гестаційна гіпертензія; прееклампсія; сприйнятий стрес; особистісна тривожність; ситуативна тривожність; шкала тривожності Спілбергера; шкала сприйнятого стресу; психометрична оцінка; психологічне обстеження; ускладнення вагітності; психоемоційний стан; психологічний стрес; антенатальний догляд; психодіагностика